تأثير المستخلصات لبعض الأعشاب الضارة في فيزيولوجيا وإنتاج محصولي Arachis hypogaea Solanum tuberosum - حميدي، بشير (University Eloued جامعة الوادي, 2024)
الملخص: تهدف هذه الدراسة في تثمين النباتات الضارة المنتشرة بشكل واسع في الحقول الزراعية وتحسين نمو وإنتاجية المحاصيل الزراعية ذات الأهمية الغذائية والصناعية. لقد اجري هذا البحث في دراسة الخصائص الفيتوكيميائية لكل من النباتين Sonchus asper L. وCynanchum acutum L. وتأثير رش المستخلص المائي للنباتين بثلاث تراكيز مختلفة في خصائص النمو والإنتاج لكل من محصولي الفول السوداني (Arachis hypogaea L.) والبطاطس (Solanum tuberosum L.) حيث تم تصميم التجربة بالنموذج القطاع العشوائي التام واعتمد في التحليل الإحصائي على اختبار ANOVA في الاكسل. قد بينت النتائج أن الجزء الهوائي للنباتين لديهما محتوى عالي من الماء والمادة العضوية إضافة إلى المادة المعدنية، كما لهما قيمة غذائية عالية وان محتوى الكربوهيدرات أعلى في مستخلص نبات Sonchus asper L. في حين محتوى البروتينات أعلى عند نبات Cynanchum acutum L. كما بينت النتائج غنى النباتين بمركبات الأيض الثانوي والمحتوى العالي من الفينولات والفلافونويدات والعفصيات. وأن للمستخلصين قدرة ارجاعية عالية باختبار DPPH* وFRAP . أما من ناحية تأثير مستخلص النباتين على محصول الفول السوداني فقد تبين أن للمستخلص المائي لكلا النباتين أثر أليلوباثي تثبيطي في خصائص إنبات البذور لمحصول الفول السوداني كلما زاد التركيز إضافة إلى خصائص النمو الخضري والإنتاج وكذلك الخصائص الفيزيوكيميائية ومحتوى الفلافونويدات بالبذور ما عدا محتوى الفينولات يزداد عند التركيز 15 mg/ml في حين أن اثر الرش للمستخلص النبات على محصول البطاطس فقد أوضحت النتائج تناقص في خصائص النمو الخضري المتمثلة في عدد ومساحة الأوراق وطول الساق وخصائص الإنتاج ونسبه المادة الجافة إضافة إلى القيمة الغذائية والفلافونويدات، بينما يزداد محتوى الرماد وعدد الأفرع ومحتوى الفينولات عند التركيز 15 mg/ml، إما خصائص عدد الدرنات وعدد الأوراق طول الشجيرات لا يستجيب لعملية الرش. عموما تبين أن للنباتين Sonchus asper L. وCynanchum acutum L. ذات أهمية واعدة من الناحية الطبية الزراعية واستعمالها كمبيدات عشبية طبيعية للتقليل من الأعشاب الضارة دون اعتبارها كسماد عضوي. Abstract This study aims to assess the value of widely spread harmful plants in agricultural fields and to improve the growth and productivity of agriculturally and industrially important crops. This research was conducted to study the phytochemical properties of the two plants Sonchus asper L. and Cynanchum acutum L., and the effect of spraying their aqueous extracts at three different concentrations on the growth and production characteristics of two crops: peanut (Arachis hypogaea L.) and potato (Solanum tuberosum L.). The experiment was designed using a completely randomized block design, and the statistical analysis was based on the ANOVA test in Excel. The results showed that the aerial parts of the plants have a high water content, organic matter, and mineral content, in addition to high nutritional value. The carbohydrate content was higher in the extract of Sonchus asper L., while the protein content was higher in Cynanchum acutum L.. The results also indicated that both plants are rich in secondary metabolites, with high levels of phenolics, flavonoids, and tannins. The extracts exhibited strong reducing power in the DPPH* and FRAP assays. Regarding the effect of the plant extracts on peanut crops, it was found that the aqueous extract of both plants had an allelopathic inhibitory effect on seed germination characteristics of peanut crops, which increased with concentration, in addition to affecting vegetative growth characteristics, production, and chemical properties, as well as flavonoid content in seeds. However, phenolic content increased at a concentration of 15 mg/ml. As for the effect of spraying the plant extract on potato crops, the results showed a decrease in vegetative growth characteristics, represented by the number and area of leaves, stem length, production characteristics, dry matter percentage, as well as nutritional value and flavonoid content. Meanwhile, ash content, the number of branches, and phenolic content increased at a concentration of 15 mg/ml. However, the characteristics of tuber number and leaf number and plant height did not respond to the spraying process. Overall, it was found that Sonchus asper L. and Cynanchum acutum L. have promising agricultural and medicinal importance and can be used as natural herbicides to reduce weeds without considering them as organic fertilizers..
أطروحة دكتوراه
Keywords: Cynanchum acutum L.; Sonchus asper L.; Arachis hypogaea L.; Solanum tuberosum L.; Allelopathic.